Physicochemical and Functional Characterization of Female Reproductive Fluids: A Report of the First Two Infants Born Following Addition of Their Mother's Fluids to the Embryo Culture Media - Canha-Gouveia, Analuce; Prieto-Sánchez, Maria Teresa; Sánchez-Ferrer, Maria Luisa; Mollá, Marta; Martínez-Soto, Juan Carlos; París-Oller, Evelyne; Soriano-Úbeda, Cristina; Landeras, José; Coy, Pilar (Frontiers in Physiology, 2021)
Culture media supplemented with reproductive fluids (RF) have been used in livestock species, improving the efficiency and quality of the in vitro produced embryos. However, its usefulness in humans it is still unknown. Here we collected human reproductive fluids (HRF) ex vivo (in 25 patients undergoing abdominal hysterectomy plus bilateral salpingectomy) and in vivo (in 31 oocyte donors). Afterward, the protocols to evaluate their osmolality, pH, total protein concentration, endotoxin level, and sterility were optimized, establishing the security ranges for their use as natural additives. Also, a functional assay was developed with bovine embryos grown in a medium supplemented with 1% HRF collected in vitro. Finally, a proof of concept was performed with eight patients at day 2 post-ovulation to evaluate the full-term viability of embryos grown in media supplemented with autologous uterine fluid, collected under in vivo conditions. Two of those embryos resulted in successful pregnancy and delivery of healthy babies. In conclusion, this study establishes a complete quality control sheet of HRF as additives for embryo culture media and shows the first preliminary data about the obtaining of healthy offspring derived from embryos grown in media supplemented with HRF.